2020
DOI: 10.1101/2020.08.02.232645
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Host metabolic reprogramming in response to SARS-Cov-2 infection

Abstract: Understanding the pathogenesis of SARS-CoV-2 is important for developing effective treatment strategies. Viruses hijack the host metabolism to redirect the resources for their replication and survival. How SARS-CoV-2 influences the host metabolism is still unclear. In this study, we analyzed transcriptomic data obtained from different human respiratory cell lines and patient samples (Swab, PBMC, lung biopsy, BALF) to understand the metabolic alterations in response to SARS-CoV-2 infection. For this purpose, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 78 publications
(68 reference statements)
0
11
0
Order By: Relevance
“…This lymphopenia may be connected to dysfunctional cell metabolism of different immune effector cells. Recent gene expression studies have also shown evidence for metabolic changes in COVID-19 patients (Gardinassi et al 2020;Moolamalla et al 2020). However, few studies have investigated how metabolic processes might be correlated to the host immune response to SARS-CoV-2 infection.…”
Section: Resultsmentioning
confidence: 99%
“…This lymphopenia may be connected to dysfunctional cell metabolism of different immune effector cells. Recent gene expression studies have also shown evidence for metabolic changes in COVID-19 patients (Gardinassi et al 2020;Moolamalla et al 2020). However, few studies have investigated how metabolic processes might be correlated to the host immune response to SARS-CoV-2 infection.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the Warburg effect has been identified as having a key role in SARS-CoV-2 replication and associated inflammatory response [46]. Others have demonstrated the downregulation of the pentose phosphate pathway [47]. While others have reported the role of nicotinate metabolism linked to inflammatory signals [33].…”
Section: Specificity Of Sars-cov-2 Virus Isolatesmentioning
confidence: 99%
“…Our data are in agreement with previous results showing virus-induced metabolic reprogramming in the host. The increased abundance of metabolites and their pathways, such as free fatty acids and amino acids, was correlated to the increase in viral proliferation, since these biomolecules can act as building blocks and fuel for this process [141][142][143] .…”
Section: Additional Informationmentioning
confidence: 99%